Linking High Risk Postpartum Women with a Technology Enabled Health Coaching Program to Reduce Diabetes Risk and Improve Wellbeing: Program Description, Case Studies, and Recommendations for Community Health Coaching Programs - Priyanka Athavale; Melanie Thomas; Adriana T. Delgadillo-Duenas; Karen Leong; Adriana Najmabadi; Elizabeth Harleman; Christina Rios; Judy Quan; Catalina Soria; Margaret A. Handley (Journal of Diabetes Research)
Background. Low-income minority women with prior gestational diabetes mellitus (pGDM) or high BMIs have increased risk for chronic illnesses postpartum. Although the Diabetes Prevention Program (DPP) provides an evidence-based model for reducing diabetes risk, few community-based interventions have adapted this program for pGDM women. Methods. STAR MAMA is an ongoing randomized control trial (RCT) evaluating a hybrid HIT/Health Coaching DPP-based 20-week postpartum program for diabetes prevention compared with education from written materials at baseline. Eligibility includes women 18–39 years old, ≥32 weeks pregnant, and GDM or BMI > 25. Clinic- and community-based recruitment in San Francisco and Sonoma Counties targets 180 women. Sociodemographic and health coaching data from a preliminary sample are presented. Results. Most of the 86 women included to date (88%) have GDM, 80% were identified as Hispanic/Latina, 78% have migrant status, and most are Spanish-speaking. Women receiving the intervention indicate high engagement, with 86% answering 1+ calls. Health coaching callbacks last an average of 9 minutes with range of topics discussed. Case studies presented convey a range of emotional, instrumental, and health literacy-related supports offered by health coaches. Discussion. The DPP-adapted HIT/health coaching model highlights the possibility and challenge of delivering DPP content to postpartum women in community settings. This trial is registered with ClinicalTrials.gov NCT02240420.